Role of Information Communication and Technology (ICT) in the Treatment of Brain Ailments - Srivastav, Narayani; Urooj, Shabana (International Journal of Medical Research and Review, 2017)
The emphasis on understanding the human brain and its functioning has been captivating since ages. Rising to this challenge, it gives us an insight of who we are. Significant and profound research is taking place in medical field to understand the structure and functioning of the brain in micro detailing aspect. There are many techniques and methodologies used in the study and diagnosis of brain ailments. ICT has proven to be a strong and supportive hand in this field for better understanding and analysis. In this paper the role of ICT in the field of neuro-sciences has been elaborated.